KONSEP UANG DAN KEBIJAKAN MONETER DALAM EKONOMI ISLAM - Sitti Nikmah Marzuki (AL-IQTISHAD, 2020)
AbstractMoney has a very important position in the economy so thatthe Islamic economy money is used for transactions and security.Money is not a commodity that has a price, therefore money cannotbe traded. Money is the public‘s goods, money that is not productive(idle assets) will be taxed so that the number will be reduced,therefore the money should be utilized in the productive sector / realsector (flow concept). The main difference of conventional monetary policy andIslamic monetary policy is the Islamic policy does not recognize theexistence of interest rate instruments as it is clear in the Qur‘an thatusury is forbidden or haram. The wisdom behind the prohibition ofusury is to create partnership relationship between the owners ofcapital and businessmen fairly. A number of conventional monetarypolicy instrument according to Islamic economists such as ReserveRequirement, overalls and selecting credit ceiling, moral suasion andchange in monetary base, equity-based type of securities can still heused to control money and credit, as long as it follows the principlesof Islamic transactions include Wadiah, Musharaka, Mudaraba, arRahn, and al-Ijarah. Kata Kunci: Uang; Kebijakan Moneter; Ekonomi Islam